Utility of serum galactomannan in diagnosing invasive aspergillosis among hematology patients: a meta-analysis - Dikmeer, Ayşe; Durusu Tanrıöver, Mine; Aşçıoğlu, Sibel (Acta Medica, 2025)
Objective: In immunocompromised patients, invasive aspergillosis (IA) is a leading cause of morbidity and mortality. The serum galactomannan (GM) assay is a non-invasive test that may assist in IA diagnosis. The purpose of this meta-analysis is to determine the diagnostic accuracy of the serum GM in patients with hematological malignancies. Materials and Methods: A search was conducted in the MEDLINE database through PubMed. After selection process and data extraction, 2x2 tables were constructed for patients with proven/probable IA and no IA, as well as for patients with proven IA and no IA. The pooled sensitivity and specificity were established using meta-analysis for the cut-off values of 0.5,1.0 and 1.5 ODI. Inter-study heterogeneity was assessed utilizing the inconsistency test (I2). The receiver operating characteristic (ROC) curve was generated, and the area under the curve (AUC) was calculated. The data analysis was conducted using the Meta-DiSc 1.4 software. Results: A total of 26 articles, 4502 patients and controls, together with 4761 IA episodes, were included in the meta-analysis. The total number of patients with proven and probable IA was 633 (13.3%). In the group with proven/probable IA versus no-IA, the overall pooled sensitivity and specificity were 80% and 78% (AUC: 0.892) for 0.5 ODI, 74% and 96% (AUC: 0.959) for 1.0 ODI, and 70% and 96% (AUC: 0.964) for 1.5 ODI, respectively. In the group with proven versus no-IA, the overall pooled sensitivity and specificity were 94% and 76% (AUC: 0.922) for 0.5 ODI, 86% and 96% (AUC: 0.979) for 1.0 ODI and 70% and 96% (AUC: 0.974) for 1.5 ODI, respectively. Conclusion: Our findings indicate that the most appropriate cut-off value for Serum GM in diagnosing IA is 1.0 ODI.